SARS‐CoV‐2 evades immune detection in alveolar macrophages. (28th October 2020) - Dalskov, Louise; Møhlenberg, Michelle; Thyrsted, Jacob; Blay‐Cadanet, Julia; Poulsen, Ebbe Toftgaard; Folkersen, Birgitte Holst; Skaarup, Søren Helbo; Olagnier, David; Reinert, Line; Enghild, Jan Johannes; Hoffmann, Hans Jürgen; Holm, Christian Kanstrup; et al.
Abstract: Respiratory infections, like the current COVID‐19 pandemic, target epithelial cells in the respiratory tract. Alveolar macrophages (AMs) are tissue‐resident macrophages located within the lung. They play a key role in the early phases of an immune response to respiratory viruses. AMs are likely the first immune cells to encounter SARS‐CoV‐2 during an infection, and their reaction to the virus will have a profound impact on the outcome of the infection. Interferons (IFNs) are antiviral cytokines and among the first cytokines produced upon viral infection. In this study, AMs from non‐infectious donors are challenged with SARS‐CoV‐2. We demonstrate that challenged AMs are incapable of sensing SARS‐CoV‐2 and of producing an IFN response in contrast to other respiratory viruses, like influenza A virus and Sendai virus, which trigger a robust IFN response. The absence of IFN production in AMs upon challenge with SARS‐CoV‐2 could explain the initial asymptotic phase observed during COVID‐19 and argues against AMs being the sources of pro‐inflammatory cytokines later during infection. Synopsis: Alveolar macrophages produce interferons and activate interferon stimulated genes when challenged with influenza A virus or Sendai virus, but not when challenged with SARS‐CoV‐2, suggesting that its genomic RNA is undetectable for innate immune sensors. Alveolar macrophages do not produce IFNs or activate ISGs when challenged with SARS‐CoV‐2. SARS‐CoV‐2 challenge does not lead to a productive infection in alveolar macrophages. The absence of IFN induction suggests that SARS‐CoV‐2 genomic RNA is not sensed in AMs. Abstract : Alveolar macrophages produce interferons and activate interferon stimulated genes when challenged with influenza A virus or Sendai virus, but not when challenged with SARS‐CoV‐2, suggesting that its genomic RNA is undetectable for innate immune sensors.